Civil excavations and tunnelling : a practical guide - Tatiya, Ratan (Thomas Telford ; Distributed in the USA by ASCE Press, 2005)
This is a comprehensive text on civil excavations at the surface as well as subsurface locales. Including tunnels that could be created with or without aid of explosives using latest methods equipment and techniques with due consideration to safety and environment.